THE LONG-TIME EFFECT OF MASK-WEARING DURING COVID-19 PANDEMIC ON THE ACNE INCIDENCE OF UMSU MEDICAL STUDENTS CLASS 2018 - Fadmadani, Anisa; Andrini, Nita (Medicina Biomedica Journal, 2022)
Background: A mask is a protective device that covers the mouth and nose to minimize direct transmission of infectious agents according to relevant standards. The use of masks is a fundamental non-pharmacological intervention and has proven to be effective as a barrier to transmission of viruses that cause several respiratory diseases, one of which is Coronavirus disease (COVID-19). The use of masks has been shown to have a significant protective effect, and is effective in reducing the risk and cases of COVID-19 infection. In addition to having a positive impact, the use of masks as one of the personal protective equipment (PPE) to prevent transmission and infection of COVID-19, also has a negative impact, because it causes several changes in the skin that will increase the occurrence of problems on the skin, especially in areas covered by mask. Objective: To determine the effect of the duration of using masks during the COVID-19 pandemic with the incidence of acne among students of the Faculty of Medicine, University of Muhammadiyah North Sumatra (FK UMSU) batch 2018. Methods: Analytical with cross sectional study approach, sampling method using purposive sampling technique. The data of this study were obtained from primary data using a questionnaire instrument and facial physical examination. Data analysis using Chi Square Fisher Exact test. Results: The results showed that the duration of using a mask for onethree hours, foureight hours, and more than eight hours was associated with the incidence of acne in FK UMSU students batch 2018 sequentially on 30 respondents (85.7%), 34 respondents ( 94.4%), and to 4 respondents (80%). The results of the bivariate analysis between the length of use of masks and the incidence of acne in FK UMSU students class 2018 was p = 0.260 (P0.05). Conclusion: There is no significant effect between the duration of using a mask and the incidence of acne in the 2018 UMSU Medical Faculty students.